4-(1,3-Benzothiazol-2-yl)-5-methyl-2phenyl-1-propynyl-1H-pyrazol-3(2H)-o ne - Chakib, I.; Zerzouf, A.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C20H15N3OS, is a 1H-pyrazol-3(2H)-one having aromatic 4-(1,3-benzothiazol-2-yl) and 2-phenyl substituents. The five-membered ring and the fused-ring system are close to planar, the r.m.s. deviations being 0.025 and 0.005 angstrom, respectively. The five-membered ring is aligned at 67.5 (1)degrees with respect to the phenyl ring and at 4.7 (1)degrees with respect to the fused-ring system. In the crystal, adjacent molecules are linked through the acetylenic H atom by a C-H center dot center dot center dot O hydrogen bond into C(8) chains propagating in [010].